HARMONIZATION AND STANDARDIZATION OF LEGISLATION ON BANKRUPTCY AS AN IMPORTANT SEGMENT TO EU INTEGRATION FOR COUNTRIES IN SOUTH/EASTERN EUROPE: A CASE STUDY OF KOSOVO - Krasniqi, Armand (European Scientific Journal, ESJ, 2015)
The paper is focused on judicial theoretical approaches on legislation of the South-East countries of Europe, specifically in Kosovo. It regulates the issue of bankruptcy and re-organization of enterprises based on this process. This was because, according to our pretense, it is the most underdeveloped legislation in this part of the Balkans. There are no doubts that there are states in the South-East Europe that achieved results in the sphere of modernization of the legislation. However, it was regulated by business which includes business activities, registration, and operation of business enterprises. However, it is uncontested that the issue of bankruptcy remains a segment that is regulated in each country according to the perceptions and concepts they have related to their own legal systems. Apart from the differences identified by concrete, formal, procedural, and material disposals, the issue has become complicated when we talk about judiciary that proceeds with the process of bankruptcy. Up until now, it has not noticed any initiative related to the harmonization and standardization according to model laws UNCITRAL. At least up until now, there are no recommendations or guidelines regarding the improvements, harmonization, and standardization of legislation made by relevant international institutions for the countries that aspires for EU integration. It is important that countries in South-East Europe, including Kosovo, should urgently review this segment of legal system through common shares, assisted by UNCITRAL. This is in accordance with the principles of model law on bankruptcy UNCITRAL, to harmonize and standardize legislation on bankruptcy.